A New Approach for Resolving a Supplier Selection and Evaluation Problem - Ketata, Raouf; Ben Mahmoud, Hajer; Ben Romdhan, Taieb (Malaysian Journal of Computer Science, 2008)
In order to select the best suppliers it is necessary to make a trade off between these tangible and intangible factors some of which may conflict. This article proposes a new approach based on the integration of the fuzzy logic with the classical multi-criteria methods on the one hand and taking into account the concept of supplier reliability for resolving a supplier selection and evaluation problem on the other hand. Indeed, we deal with the first approach called "Method with Constraints" (MC) which consists of combination of the "Fuzzy Analytical Hierarchy Process" (FAHP) with the "Goal Programming" (GP) methods. This method reflects the idea of supplier reliability and at the same time the quantitative and qualitative factors. Considering the fuzzy constraints, we propose the second approach called "Method with Fuzzy Constraint" (MCF) which consists of combination of the FAHP with the "Fuzzy Goal Programming" (FGP) methods. We used the gravity centre method to approach the best solution, the supplier reliability approach to identify the most reliable supplier and the fuzzy logic method to find solutions for the inaccuracy and uncertainty problems. A numerical example is presented to illustrate this new approach which includes comparing the advantages and disadvantages of the selection methods for resolving a supplier selection and evaluation problem.